Website Development of Songkran Festival, Ban Prue, Prue Sub-District, Prasat District, Surin Province - Panleow, Juntakan (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The purposes of the research were 1) to develop Songkran Festival website, in the title of Ban Prue, Prue Sub-district, Prasat District, Surin Province. 2) To study the Ban Khlong School teachers’ satisfaction, Prue Sub-district, Prasat District, Surin Province towards the title of Ban Prue New Year Songkran Festival, Prue Subdistrict, Prasat District, Surin Province. The research instruments were websites developed with Adobe Photoshop CS6, Adobe Dreamweaver CS6, Adobe Flash CS, and Sony Vegas Pro. The satisfaction assessment was questionnaire for website user and focuses on eight areas. The sample group consisted of 16 teachers at Ban Khlong School, Prue Subdistrict, Prasat District, Surin Province. The statistics used in the data analysis were percentage, mean and standard deviation. The research findings showed that the Songkran Festival website, Ban Prue, Prue Sub-district, Prasat District, Surin Province. The teachers’ satisfaction was at a high level in overall and each area at a high level of 4.13. The highest average in Content Accessibility was satisfied a high level (4.25), Web Page Design (4.19), Font is (4.19), Video (4.16), Website Content (4.16), Language (4.13), Illustration (4.08) and the sound was the lowest level (3.88).